Navigating Surgical Decision Making in Disorders of Sex Development (DSD) - Gardner, Melissa; Sandberg, David E. (Frontiers in Pediatrics, 2018)
Surgical management of disorders of sex development (DSD) is associated with contentious debate between and within stakeholder communities. While the intent of surgical management of the genitals and gonads is to benefit the patient physically and psychosocially, these goals have not always been achieved; reports of harm have surfaced. Harm experienced by some patients has resulted in the emergence of an activist platform calling for a moratorium on all surgical procedures during childhood – excepting those forestalling threats to life within the childhood years. This ban is not universally endorsed by patient advocacy groups. Parents, meanwhile, continue to need to make decisions regarding surgical options for their young children. Constructive paths forward include implementation of Consensus Statement recommendations that call for comprehensive and integrated team care, incorporating mental health services and adopting shared decision making.